1992
DOI: 10.1002/ijc.2910500620
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelioma in rats following intrapleural injection of chrysotile and phosphorylated chrysotile (chrysophosphate)

Abstract: Pathological effects of asbestos are probably dependent on the size and surface properties of the fibers. Surface-modified chrysotile fibers were injected into the pleural cavity of rats to investigate the potency of the fiber to induce mesothelioma. Chrysotile fibers were modified by a phosphorylation process, resulting in the presence of phosphorus at the fiber surface. Phosphorylated samples were characterized by enhanced durability and reduced affinity for biological macromolecules. Five samples were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The important role of fibers corresponding to Stanton’s criteria (L > 8 μm; d ≤ 0.25 μm) has been evidenced in other reports where asbestos fibers were injected in the pleural cavity [74-76]. In these studies, other factors playing a role in the toxicity of fibers were identified and investigated.…”
Section: Introductionmentioning
confidence: 84%
“…The important role of fibers corresponding to Stanton’s criteria (L > 8 μm; d ≤ 0.25 μm) has been evidenced in other reports where asbestos fibers were injected in the pleural cavity [74-76]. In these studies, other factors playing a role in the toxicity of fibers were identified and investigated.…”
Section: Introductionmentioning
confidence: 84%
“…By intrapleural inoculation, it has been concluded that the probability of tumor formation was dependent on fiber size, based on results obtained with MMF and asbestos (21); this assumption was confirmed recently (35,36,71). Asbestos used as positive control entailed a globally significant tumor enhancement, except in SW and RW studies (13).…”
Section: Discussionmentioning
confidence: 80%
“…Erionite was found to induce MM in rodents both by injection into the pleural or peritoneal cavities and by inhalation (Wagner et al, 1985; Johnson et al, 1984; Maltoni et al, 1982; Van der Meeren et al, 1992). Further investigations in rodents showed that erionite disrupts the balance between cell proliferation and apoptosis toward cell proliferation.…”
Section: Erionite In An MM Epidemicmentioning
confidence: 99%